The Impact of Maternal Self-Efficacy and Oral Health Beliefs on Early Childhood Caries in Latino Children - Wilson, Anne R.; Mulvahill, Matthew J.; Tiwari, Tamanna (Frontiers in Public Health, 2017)
Objectives: Latino children experience one of the highest rates of early childhood caries requiring interventions based on valid conceptual frameworks. The Health Belief Model has relevance as a predictor of compliance with health recommendations based on perceptions of a health condition and behaviors to avoid the condition. The model encompasses four perceptual constructs (susceptibility, severity, benefits, barriers) and for complex conditions, includes self-efficacy as an extended model. This study evaluated individual (self-efficacy and health beliefs) and cultural (acculturation status) level factors and the inter-relationship to determine if items assessed for the extended health belief model were valid measures of maternal factors. Methods: A cross-sectional study was conducted with 100 mother-child dyads at the Dental Center of Children’s Hospital Colorado, Aurora, Colorado. Participating mothers completed a survey in English or Spanish with items from the Basic Research Factors Questionnaire encompassing sociodemographic characteristics, oral health knowledge and behavior, and psychosocial measures including the extended health belief model. Language preference was a proxy for maternal acculturation. Children were examined to measure decayed, missing and filled tooth surfaces. Internal consistency reliability of each subscale was evaluated using Cronbach’s alpha. Convergent validity was assessed using linear regression to evaluate the association of the extended health belief model subscales with oral health-related measures and language preference. Results: The benefits and self-efficacy scales reflected good reliability. Maternal education was the strongest predictor of health beliefs with significant associations for barriers, benefits, and susceptibility. Perceived benefits increased with each additional year in the household. There was a significant association between maternal oral health knowledge and higher perceived benefits and increased self-efficacy, and the same was found for higher knowledge of dental utilization which was also associated with children perceived as having increased susceptibility to early childhood caries. Less acculturated participants perceived more barriers to behavioral adherence and fewer barriers as knowledge increased. As dental utilization knowledge improved for Spanish-speaking participants, they perceived greater benefits from adherent oral health behavior compared to English-speaking participants. Conclusions: Items assessed for the extended health belief model were valid as measures of maternal factors influencing children’s oral health outcomes in a Latino population.